Pengaruh Pembelajaran Daring Terhadap Hasil Belajar Siswa Kelas IV di Sekolah Dasar Negeri 70 Palembang - Kustiyandari, Aisyiah; Hermansah, Bambang; Marleni, Marleni (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
This online or distance learning began on March 16, 2020, based on the decision of the Minister ofEducation and Culture of the Republic of Indonesia regarding Circular Letter Number 4 of 2020 concerning the Implementation of Educational Policies in the Emergency Period for the Spread of Corona Virus Disease (COVID-19). The purpose of this study was to determine and describe the effect of online learning on the learning outcomes of fourth grade students at 70 Palembang Elementary School. The research method used in this study is a quantitative descriptive method. The results showed thatonline learning had a negative effect on the fourth grade student learning outcomes of SD Negeri 70Palembang. In other words, if SD Negeri 70 Palembang continues to conduct online learning, the learning outcomes of fourth grade students will continue to decline and vice versa.